Flow and heat transfer simulation in rotating disks with/without enclosure - Liu, Zhi Yong. (2008)
The flow structure, heat transfer and wall friction in disks are being investigated thoroughly. As computer industry demands for hard disk drive (HDD) is increasing every day with the rapid progress of high rotational speed and high capacity of HDD, it is important to design optimal configuration of HDD based on good understanding of the flow structure with thermal constraint. For example, investigations of such can show where the region with high temperature is and how this is modified with optimal constraints. However, hitherto there is little research on such field due to the complex situation with high rotational speed.